2016
DOI: 10.1105/tpc.15.00880
|View full text |Cite
|
Sign up to set email alerts
|

Dual and Opposing Roles of Xanthine Dehydrogenase in Defense-Associated Reactive Oxygen Species Metabolism in Arabidopsis

Abstract: While plants produce reactive oxygen species (ROS) for stress signaling and pathogen defense, they need to remove excessive ROS induced during stress responses in order to minimize oxidative damage. How can plants fine-tune this balance and meet such conflicting needs? Here, we show that XANTHINE DEHYDROGENASE1 (XDH1) in Arabidopsis thaliana appears to play spatially opposite roles to serve this purpose. Through a large-scale genetic screen, we identified three missense mutations in XDH1 that impair XDH1's enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 80 publications
1
72
1
Order By: Relevance
“…An increase in L-tryptophan content in N-deficiency conditions is probably associated with amino acids acting synergically to mitigate N-deficiency damage of plants. Purine metabolism is part of nitrogen metabolism, and the relative metabolites synthesis is closely linked to nitrogen availability (Ma et al, 2016). We found that the abundances of adenosine, deoxyadenosine and hypoxanthine were significantly different both in roots and leaves.…”
Section: Primary Metabolic Pathway and Metabolites Analysismentioning
confidence: 77%
“…An increase in L-tryptophan content in N-deficiency conditions is probably associated with amino acids acting synergically to mitigate N-deficiency damage of plants. Purine metabolism is part of nitrogen metabolism, and the relative metabolites synthesis is closely linked to nitrogen availability (Ma et al, 2016). We found that the abundances of adenosine, deoxyadenosine and hypoxanthine were significantly different both in roots and leaves.…”
Section: Primary Metabolic Pathway and Metabolites Analysismentioning
confidence: 77%
“…The following T-DNA mutants of A. thaliana from the SALK collection (Alonso et al, 2003) and from the GABI-Kat collection (Kleinboelting et al, 2012) were used: SALK007531C, rbsk-1 (Riggs et al, 2016); SALK083120, nsh1-1 (Jung et al, 2011), SALK036597C, cda-2 (Chen et al, 2016); GK432D08, gsda-2 (Dahncke & Witte, 2013); GK015E03, hgprt-2 (here); GK049D04, xdh1-2 (Hauck et al, 2014;Ma et al, 2016). The first mentioning and allele assignments in the literature are cited.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…It was previously reported that plants defective in xanthine dehydrogenase (XDH), an enzyme essential for the generation of uric acid and allantoin (Werner & Witte, 2011), are susceptible to prolonged dark stress (Brychkova et al, 2008). A dual role of XDH in ROS production and in ROS protection during biotic stress has been demonstrated recently (Ma et al, 2016). However, another as yet unexplored hypothesis regarding the increased susceptibility of the NSH1 mutant to dark stress is that carbon starvation might be more severe in this mutant background, because ribose from nucleotide catabolism cannot be released to be used as a carbon source.…”
Section: Introductionmentioning
confidence: 99%
“…ABA‐induced stomatal closure is a defensive action that is usually accompanied by the production of H 2 O 2 (Li et al ., ; Zhang et al ., ). NADPH oxidase (RbohF) can generate H 2 O 2 in guard cells, which crucially modulates ABA‐induced stomatal closure and plant drought tolerance (Gudesblat et al ., ; Kolla et al ., ; Ma et al ., ). Previous studies have indicated that AtRbohF can be phosphorylated by OST1 (an ABA‐induced SnRK2.6 protein kinase) (Joshi‐Saha et al ., ; Sirichandra et al ., ; Wege et al ., ).…”
Section: Introductionmentioning
confidence: 97%